2017
DOI: 10.5530/jyp.2017.9.15
|View full text |Cite
|
Sign up to set email alerts
|

Development of Nanoparticulate Hydrogel Loaded with Crossandra infundibuliformis Extract

Abstract: Objective: Present study is aimed at formulation of hydrogel containing PLGA nanoparticles loaded with of Crossandra infundibuliformis (CI) extract. Leaf extract of Crossandra infundibuliformis has been reported to possess antibacterial, antifungal activity hence an attempt was done to improve the efficacy of the extract by formulating into nanoparticulate hydrogel which can be used as a feasible alternative to conventional formulations of Crossandra infundibuliformis extract with dual benefit of sustained rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…In the present study, the OEG2 and OEEG2 showed particle sizes of 196.7 nm and 186.7 nm. The size of polymeric nanoparticles ranges from 100 to 1,000 nm providing a stable colloidal dispersion ( Jyothi et al, 2017 ; Saha et al, 2023 ). The zeta potential was carried out to measure the surface charge of the formulated hydrogel.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, the OEG2 and OEEG2 showed particle sizes of 196.7 nm and 186.7 nm. The size of polymeric nanoparticles ranges from 100 to 1,000 nm providing a stable colloidal dispersion ( Jyothi et al, 2017 ; Saha et al, 2023 ). The zeta potential was carried out to measure the surface charge of the formulated hydrogel.…”
Section: Resultsmentioning
confidence: 99%
“…To understand the release mechanism of QCT from AgNPs hydrogel, data were fitted in different release kinetic models like zero-order, first order, Korsmeyer-Peppas, Hixon Crowell and Higuchi, and the model with the highest value of correlation coefficient (r 2 ) was taken as the best fit model [32].…”
Section: 74mentioning
confidence: 99%
“…PLGA nanoparticles loaded with C . infundibuliformis incorporated into the hydroxypropyl methylcellulose K4M (HPMC K4M) hydrogels and studied the in vitro drug release studies, and according to the results, the amount of cumulated drug released from the prepared hydrogel formulation over 24 hours was 90.06% whereas drug release from the extract solution was found to be 95.13% within 6 hours and reached 99.66% by 24 hours …”
Section: Herbal Extract‐incorporated Polymeric Nanoparticlesmentioning
confidence: 99%